Analysis of Patient Satisfaction with Nursing Services at Eka Hospital Cibubur Outpatient Unit: A SERVQUAL Method - Arif Sujadi; Elsya Fernita Rosanti; Erika Fitria (Sekolah Tinggi Ilmu Kesehatan Sumber Waras, 2025)
Patient satisfaction is one of the key indicators for assessing the quality of hospital services and influences its competitiveness. This study aims to analyze the gap between patient expectations and reality regarding nursing services at the Eka Hospital Cibubur Polyclinic. This study is quantitative and uses the SERVQUAL (service quality) method to measure patient satisfaction based on five dimensions: Tangible, Responsiveness, Reliability, Assurance, and Empathy. The study sample used an accidental sampling technique obtained by 89 respondents participating by completing an online questionnaire. The results showed that the average patient expectation value was 4.52, while the average reality value was 4.39, resulting in a SERVQUAL gap of (-0.13). Based on the results, improvements are still needed related to services to increase patient satisfaction. However, the level of conformity between expectations and reality reached 97%, which indicates that overall, the service is in accordance with patient expectations. Keywords: Patient satisfaction, SERVQUAL, Service quality, Eka Hospital Cibubur